A ética face ao preconceito contra a diversidade: um estudo na perspectiva dos filósofos da educação - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
This article aims to discuss the importance of ethics for high school, seeking to highlight what meanings and meanings it presents in the fight against the various types of prejudice still existing in society, especially in educational institutions. The discussion is imperative, as it highlights the importance of ethical reflection in this specific segment, given its great socioeducational diversity. The proposal of work was born from the question: How can ethics contribute to minimize prejudice against socio-educational diversity in high schools? In view of this, the study is a bibliographical research on diverse sources of authors and philosophers of contemporary education, which deal with the theme presented, aiming at a broader discussion of the problem presented. In this sense, the discussion becomes relevant both to the understanding of the multiplicity of concepts that involve ethics in relations in society, as well as to the understanding about the numerous types of prejudices against sociocultural diversity, such as racism, homophobia, misogyny, xenophobia , machismo, social class and others still existing in the school environment, and also to the perception of how ethics can constitute an effective instrument in the fight against these prejudices in the context of high schools.
Keywords: Ética; Preconceito; Ensino médio; Diversidade